Answer:
Here's what I get
Step-by-step explanation:
1. Molecular equation
3(NH₄)₂CO₃(aq) +2FeCl₃(aq) ⟶ 6NH₄Cl(aq) + Fe₂(CO₃)₃(aq)
2. Ionic equation
You write molecular formulas for the solids, and you write the soluble ionic substances as ions.
6NH₄⁺(aq) + 3CO₃²⁻(aq) + 2Fe³⁺(aq) + 6Cl⁻(aq) ⟶ 6NH₄⁺(aq) + 6Cl⁻(aq) + Fe₂(CO₃)₃(s)
3. Net ionic equation
To get the net ionic equation, you cancel the ions that appear on each side of the ionic equation.
6NH₄⁺(aq) + 3CO₃²⁻(aq) + 2Fe³⁺(aq) + 6Cl⁻(aq) ⟶ 6NH₄⁺(aq) + 6Cl⁻(aq) + Fe₂(CO₃)₃(s)
The net ionic equation is
2Fe³⁺(aq) + 3CO₃²⁻(aq) ⟶ Fe₂(CO₃)₃(s)